1992
DOI: 10.1002/hep.1840150105
|View full text |Cite
|
Sign up to set email alerts
|

Improved detection of hepatitis c virus antibodies in high-risk populations

Abstract: Sera from 483 patients at high (group 1, n = 313) and lower (group 2, n = 170) risk for exposure to hepatitis C were tested for antibodies to hepatitis C using first-generation (c100-3) and second-generation enzyme-linked immunosorbent assays and four-antigen recombinant immunoblot assay. The second-generation enzyme-linked immunosorbent assay and nitrocellulose-based immunoblot assay differ from c100-3-based systems in the addition of expression products from the NS3/NS4 (c33c, c200) and putative nucleocapsid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
0

Year Published

1993
1993
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(38 citation statements)
references
References 28 publications
3
35
0
Order By: Relevance
“…C33c and C22-3 blots in RIBA-2 are reported to be more sensitive than C100-3 or 5-1-1 blot in identifying sera contaminated with HCV (26). Marvelously, antibodies to C33c and C22-3 were detected in all 155 sera with viremia in the present study.…”
Section: Discussionsupporting
confidence: 48%
“…C33c and C22-3 blots in RIBA-2 are reported to be more sensitive than C100-3 or 5-1-1 blot in identifying sera contaminated with HCV (26). Marvelously, antibodies to C33c and C22-3 were detected in all 155 sera with viremia in the present study.…”
Section: Discussionsupporting
confidence: 48%
“…Second generation EIA test for HCV antibody yields greater specificity and sensitivity. However, McHUTCHISON et al 15 found little improvement in specificity when testing a low-risk population, although a correlation between optical density values and the presence of HCV RNA was observed.…”
Section: Discussionmentioning
confidence: 99%
“…The average period for HCV seroconversion after blood transfusion has been shortened with each new generation: 7 to 8 weeks for EIA-3 compared with 10 weeks for EIA-2 and 16 weeks for EIA-1 8 . Incorporating these new antigens improved the sensitivity of the assay but the question of specificity remains open 6,8,15 . Thus, in EIA-positive cases, it is important to confirm these tests results using other assays.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies of anti-HCV EIA assays also noted that individuals with low-positive results were typically negative when tested by RIBA or HCV RNA (28,29 ). Package inserts from manufacturers indicate this fact but do not suggest reporting results along with S/C ratio or supplementary testing in individuals with lowpositive anti-HCV EIA results.…”
Section: Discussionmentioning
confidence: 99%